Epidemiology of Bloodstream Infections in Kidney Transplant Recipients: A Systematic Review and Meta-analysis. (4th October 2017) - Sandkovsky, Uriel; Qiu, Fang; Kalil, Andre C; Weinfeld-Massaia, Adriana; Kwon, Joong; Schmidt, Cynthia; Florescu, Diana F
Abstract: Background: Infections represent the major cause of morbidity and mortality among solid organ transplant recipients. In renal transplantation, infections are the second leading cause of death after cardiovascular disease. The aim of our study was to describe the incidence of bloodstream infections after kidney transplantation and to describe the etiologic agents. Methods: We searched PubMed, Embase and Cochrane Library from inception until November 2016. Studies reporting the incidence of bloodstream infections in renal transplantation and their epidemiology were included. We excluded studies with follow-up period shorter than 1 month and duplicated data. Two investigators performed independent searches, extracted the data and entered it in a database. We used odds ratios for binary outcomes. Results: Eighty-six publications were selected for review and 60 studies (95, 044 patients) were included in the final analysis. The overall incidence of bacteremia, incidence by transplantation era and geographic regions are described in Table 1. Most bacteremias were monomicrobial and nosocomial in origin. The distribution of etiologic agents is presented in Table 2. Overall graft rejection rate (35 publications, 70, 633 patients) was 30% (95% CI 26, 33%), 1-year graft loss (25 publications, 5, 334 patients) was 7.1% (95% CI 5.3, 8.9%) and 1-year mortality (23 publications, 5, 699 patients) was 4.6% (95% CI 3.1,  6.1%). Conclusion: The incidence of bacteremia has decreased over the last 30 years but still poses a significant challenge for the management of kidney transplant recipients. The incidence of bacteremia decreased subsequently in each of the transplantation eras. Europe had the highest incidence when compared with America or Africa/Asia, probably reflecting difference in clinical practices. Most bacteremias were monomicrobial and nosocomial, predominantly Gram-negative infections; most likely these infections originated from the urinary tract. Better understanding of the epidemiology of bloodstream infections can guide preventative measures. Disclosures: All authors: No reported disclosures.